USING MODERN TECHNOLOGIES IN TEACHING MIDWIFERY SCIENCE TO ENHANCE LESSON EFFECTIVENESS (Modern education and development, 2024)
The development of education in the 21st century has seen the integration of various modern technologies into teaching and learning practices. In the field of midwifery science, the use of innovative tools and techniques has proven to be essential for improving teaching quality and student engagement. This article explores the benefits of employing modern technological approaches in midwifery education, focusing on how these tools enhance the learning experience and increase the effectiveness of lessons. Through the use of interactive platforms, digital resources, and multimedia, educators can foster a more dynamic and interactive classroom environment that caters to diverse learning styles.